Chitosan-induced biomodification on demineralized dentin to improve the adhesive interface - Isabella Rodrigues Ziotti; Vitória Leite Paschoini; Silmara Aparecida Milori Corona; Aline Evangelista Souza-Gabriel (Restorative Dentistry & Endodontics)
ObjectivesMetalloproteinase-inhibiting agents, such as chitosan, can prevent collagen degradation in demineralized dental substrates, thereby improving the adhesive interface. This study evaluated the bond strength (BS) and chemical and morphological characterization of the adhesive interface after applying chitosan solution to demineralized dentin.Materials and MethodsThe 80 third molars were selected. Forty teeth underwent caries induction using the pH cycling method. The teeth were divided according to the treatment: distilled water (control) and 2.5% chitosan solution. The surfaces were restored using adhesive and composite resins. Half of the specimens in each group were aged, and the other half underwent immediate analyses. The teeth were sectioned and underwent the microtensile bond strength test (µTBS), and chemical and morphological analyses using energy-dispersive spectroscopy and scanning electron microscopy, respectively. Data analysis was performed using 3-way analysis of variance.ResultsFor µTBS, sound dentin was superior to demineralized dentin (p < 0.001), chitosan-treated specimens had higher bond strength than the untreated ones (p < 0.001), and those that underwent immediate analysis had higher values than the aged specimens (p = 0.019). No significant differences were observed in the chemical or morphological compositions.ConclusionsChitosan treatment improved bond strength both immediately and after aging, even in demineralized dentin.